Sindh Education Sector Plans’ Conundrums toward Enhancing Equity Access to Education for All in the Region - Sohoo, Muhammed Nawaz; tagar, hamzo khan; Ali, Sheraz; Tagar, Abdul Karim; Bijarni, Ghulam Ali (Advances in Social Sciences Research Journal, 2020)
The basic aim of the paper is to critically evaluate the Sindh school education sector plans (i.e. First plan 2014-18, and second sector plan, 2019-24) as a case study. It also attempts to find missing links of enhancing education access to girls as a policy tool in greater human interest. Paper also provides recommendations for improvement in the proposed plan in public interest. The Study concludes that investment in the education of girls may well be the highest-return investment available in the developing world so plans, policies, and programs must be focused on access educational incentives to girls for sustainable economic growth and development.